O poder da cor na idade média: policromia na capela do fundador do Mosteiro da Batalha - Rodrigues, Pedro Miguel Miranda (2018)
The purpose of this dissertation is to study the Founder’s Chapel in the Monastery of Santa Maria da Vitória, Batalha, focusing on the analysis of the polychromy still existing in this space. In this sense, we introduce the theme of color in the Middle Ages, not only as a way of better understanding the place it occupies in this period, but also its relation with the artistic work, namely applied to stone, thus claiming its presence as an integral element of the medieval artistic discourse. Having the Monumental Polychomy: revealing medieval colors at Batalha project as a starting point, and the results obtained so far by Laboratório Hércules in Évora, we describe the areas of the chapel where were collected some pigments, as well as their identification and possible interpretation in the context they occupy. We also dedicate a part of this work to the analysis of the fragments of the mural painting of Prince D. Pedro altar, as well as to the vestiges of mural painting in the arcosolium of D. Henrique’s tomb. The core of this dissertation is completed with a more comprehensive analysis of what the original chapel configuration would look like in its multiple color expressions. Finally, in a third and final part of this work, taking into account the process of “marginalization” of color in stone art (from the Renaissance to the contemporary period), we explore the vicissitudes which the Monastery of Batalha has gone through, especially with restauration interventions of the nineteenth and twentieth century, as a way of understanding the loss of polychromy lining in the Avis pantheon.